Impact of diet on CVD and diabetes mortality in Latin America and the Caribbean: a comparative risk assessment analysis. Issue 9 (3rd June 2021) - Sisa, Ivan; Abeyá-Gilardon, Enrique; Fisberg, Regina M; Jackson, Maria D; Mangialavori, Guadalupe L; Sichieri, Rosely; Cudhea, Frederick; Bannuru, Raveendhara R; Ruthazer, Robin; Mozaffarian, Dariush; Singh, Gitanjali M
Abstract: Objective: To quantify diet-related burdens of cardiometabolic diseases (CMD) by country, age and sex in Latin America and the Caribbean (LAC). Design: Intakes of eleven key dietary factors were obtained from the Global Dietary Database Consortium. Aetiologic effects of dietary factors on CMD outcomes were obtained from meta-analyses. We combined these inputs with cause-specific mortality data to compute country-, age- and sex-specific absolute and proportional CMD mortality of eleven dietary factors in 1990 and 2010. Setting: Thirty-two countries in LAC. Participants: Adults aged 25 years and older. Results: In 2010, an estimated 513 371 (95 % uncertainty interval (UI) 423 286–547 841; 53·8 %) cardiometabolic deaths were related to suboptimal diet. Largest diet-related CMD burdens were related to low intake of nuts/seeds (109 831 deaths (95 % UI 71 920–121 079); 11·5 %), low fruit intake (106 285 deaths (95 % UI 94 904–112 320); 11·1 %) and high processed meat consumption (89 381 deaths (95 % UI 82 984–97 196); 9·4 %). Among countries, highest CMD burdens (deaths per million adults) attributable to diet were in Trinidad and Tobago (1779) and Guyana (1700) and the lowest were in Peru (492) and The Bahamas (504). Between 1990 and 2010, greatest decline (35 %) in diet-attributable CMD mortality was related to greater consumption of fruit, while greatest increase (7·2 %) was related to increased intakes of sugar-sweetened beverages. Conclusions: Suboptimal intakes of commonly consumed foods were associated with substantial CMD mortality in LAC with significant heterogeneity across countries. Improved access to healthful foods, such as nuts and fruits, and limits in availability of unhealthful factors, such as processed foods, would reduce diet-related burdens of CMD in LAC.